2004
DOI: 10.1136/bmj.38315.451539.f7
|View full text |Cite
|
Sign up to set email alerts
|

Parents' awareness of overweight in themselves and their children: cross sectional study within a cohort (EarlyBird 21)

Abstract: Obesity is a serious public health concern. More than half of British adults are overweight, and obesity among preschool children has increased by an alarming 70% in the past generation.1 2 We aimed to explore parents' awareness of overweight and obesity in themselves and their children, and their degree of concern about weight. Participants, methods, and resultsWe studied 277 healthy randomly recruited children (mean age 7.4 years) and parents from the EarlyBird study.3 Overweight and obesity were defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
192
10
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 3 publications
29
192
10
17
Order By: Relevance
“…30 Many parents were obviously unaware that their children were overweight, as has been observed also by others. [31][32][33] In addition, some families were not ready, mainly due to time constraints, to be randomized into the group treatment. In our area, both fathers and mothers often work outside home, and they have limited time for recurrent group sessions and even for the daily household demands.…”
Section: Discussionmentioning
confidence: 99%
“…30 Many parents were obviously unaware that their children were overweight, as has been observed also by others. [31][32][33] In addition, some families were not ready, mainly due to time constraints, to be randomized into the group treatment. In our area, both fathers and mothers often work outside home, and they have limited time for recurrent group sessions and even for the daily household demands.…”
Section: Discussionmentioning
confidence: 99%
“…more than one third of parents underestimating) are still observed across older childhood and adolescence 30, 32, 38. Likewise, although some studies have indicated that fathers are particularly likely to underestimate the weight status of their overweight child, studies repeatedly show that mothers of overweight children also frequently fail to identify that their child is overweight or obese 40, 41. Thus, as is the case with personal misperceptions of weight status, although some demographic factors have been reported to be associated with a particularly high prevalence of parental underestimation of child overweight, the failure of parents to identify adiposity is widespread 33, 38.…”
Section: Parental Underestimation Of Child Overweight and Obesitymentioning
confidence: 99%
“…However, multiple reports (mainly studying mothers) have shown a striking picture of low rates of recognition; between 17-98% of parents do not recognize overweight in their overweight children. [7][8][9][10][11] The wide range may be attributed to study differences on factors such as the obesity cut points used, child age and the method of questioning. Mothers are more accurate with older and heavier children, 10 and better at estimating body size when pictorial or photographic figures, rather than the words 'overweight' and 'obese,' are used.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers are more accurate with older and heavier children, 10 and better at estimating body size when pictorial or photographic figures, rather than the words 'overweight' and 'obese,' are used. 7 Postulated reasons for this low recognition include the normalization of overweight, denial, a genuine lack of concern or a belief that childhood 'puppy fat' is healthy; however, the evidence about the reasons remains scant. Concluding that 'the laypersons' perception of average weight and the clinical definition of overweight are now in conflict,' Jeffery reported 40% of overweight mothers and 45% of overweight fathers judged their own weight 'about right' and that a large proportion were unconcerned about their weight.…”
Section: Introductionmentioning
confidence: 99%